Kedudukan Wakil Kepala Daerah Dalam Sistem Pemerintahan Daerah Indonesia - Bait, Piere Mario; Neonbeni, Randy Vallentino (Saraq Opat: Jurnal Administrasi Publik, 2022)
In Indonesia, regional heads and deputy heads often clash when governing regional governments. This is shown in their efforts to assign people to critical positions and lack of agreement on government objectives. This study intends to clarify the role of Deputy Heads of Region in operating local governments at provincial, district, and municipal levels, as well as their connection with Heads of Region. This analysis uses statutory, conceptual, and historical methods. According to Law No. 23/2014, Article 63(1) on Regional Government, a Deputy Head of Region assists the Regional Head. In the regional government system, a Deputy Regional Head supports the Regional Head to improve regional government performance. Deputy Regional Heads must report to the Regional Head on their tasks. If the Head of a region dies, resigns, is fired, or cannot perform his or her duties for six consecutive months, the Deputy Head replaces him or her. This study's conclusions suggest a more comprehensive review of the Deputy Regional Heads' position and authority under Indonesia's regional government system. This would define the role and authority of the Deputy Regional Heads and prevent conflicts between Regional Heads and Deputy Regional Heads in Indonesia's local government system.